A new Proposition for Software Code Review Process - Nandi, Suvra; Dhar, Suvankar (International Journal of Computer Sciences and Engineering, 2025)
this paper provides a new theoretical approach of code review, considering its existing challenges in current software industry with upward trend in agile methodology adoption. This article captures both Process aspects and Technical aspects of Code Review. It tries to establish the importance of Ownership, Authority, and Transparency in Process. Technically this solution tries to identify most important four deciding factors in generating function vulnerability score with Red-Amber-Green criteria for all the four factors. It formulates easy steps of determining values for those four factors which are feasible to utilize in real life scenario. Also it explains process of identifying the fifth deciding factor based upon the outcome of a project’s defect prevention analysis. It explains ways of capturing review effectiveness by appropriate metric values which can be used for quantified reporting to senior management on a pre-defined interval